Effect of 8 weeks resistance training on serum BDNF level and memory performance in middle-aged women with metabolic syndrome - محسن ابراهیمی; پگاه میرزا علی; سید محسن آوندی (Shahid Beheshti University, 2016)
Background: The purpose of this study to verify the effects of resistance training on Serum BDNF Level andMemory Performance in Middle-aged Women with Metabolic Syndrome. Methodology: 22 volunteersmiddle-age woman with metabolic syndrome for sampling, were selected and randomly assigned to aresistance training protocol (n = 12, 43.08 ± 5.14 years, 74.13 ± 7.16 kg) or a control group (n = 10, 39.9 ±4.53 years, 82.23 ± 11.61 kg). In the resistance training protocol, ten exercises were performed, with 3 × 8-10maximal repetitions three times per week (75%_80% 1RM) With regard to the principle of overload. Shortterm, midterm and long term memory tests and also blood sampling were conducted before and after training.Data were analyzed using independent and depended t-test, analysis of variance with repeated measures 2 × 2with the level of statistical significance was set at P ≤ 0.05. Results: No significant changes in the levels ofBDNF and midterm memory in the control and exercise and control groups was not observed (P ≥ 0.05).Thedependent t test results showed a significant decrease in short term and long term memory in the exercisegroup (P ≤ 0.05), but after interactive exercise effect no significant changes was not observed (P ≥ 0.05).Conclusion: In spite of the fact the BDNF as a metatrophin, mediating the effects of exercise on cognitivefunction is known, but eight weeks of resistance training cannot have a favorable effect on increasing BDNFand memory function in middle-aged women with metabolic syndrome.